The Role of Student Management in Improving Learner Discipline and Academic Performance - Susanti Arian Fitry (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Student management is a critical component of educational management that focuses on overseeing students from admission to graduation. The primary goal of student management is to create an orderly, disciplined, and conducive learning environment that supports both academic achievement and character development. This study aims to analyze the implementation of student management in enhancing student discipline and academic performance. The research employs a library research method with a qualitative descriptive approach, analyzing relevant literature including books, journals, and previous educational studies. Data were analyzed to describe the implementation of student management, supporting and inhibiting factors, and the relationship between student management strategies and studentsâ€™ discipline and academic outcomes. The findings indicate that effective student management encompasses systematic administrative management, character development through extracurricular activities, teacher role modeling, and active parental involvement. Furthermore, the use of technology for monitoring student attendance and behavior, combined with consistent reward and sanction systems, significantly enhances student discipline. A case study at a junior high school in Aceh Tengah corroborates these findings, demonstrating that the â€œOne Day Without Violationâ€ program effectively increases studentsâ€™ awareness of positive behavior and motivation to learn. In conclusion, integrated student management that combines administrative systems, character development, and collaboration between schools and parents significantly contributes to improving both discipline and academic achievement. These results suggest that schools should continuously innovate in student management practices to create a productive and conducive learning environment for all students.